2019
DOI: 10.21098/jimf.v5i4.1111
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Outreach of Islamic Charity Based Microfinance Programs: Empirical Evidence From Indonesia

Abstract: One of the advantages of using Islamic social funds is the increased ability of microfinance institutions to provide financial services to the poor. This study aims to (1) investigates the characteristics of the clients of the Islamic Charity Based Microfinance (ICBM) program; (2) test whether the clients ICBM program are more vulnerable than the non clients group (3) discuss the rationale of why poor excluded from the zakat based microfinance program. The study was conducted in the microfinance program at zak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…QH funds can also be taken from waqf . Waqf is defined as “holding certain physical assets and preserving it to the long term benefit for the society” (Yumna and Clarke, 2009). Aside from ZIS funds, banks can therefore maximise the receipt and use of waqf .…”
Section: Discussionmentioning
confidence: 99%
“…QH funds can also be taken from waqf . Waqf is defined as “holding certain physical assets and preserving it to the long term benefit for the society” (Yumna and Clarke, 2009). Aside from ZIS funds, banks can therefore maximise the receipt and use of waqf .…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that have shown positive benefits of microfinance provision for the poor in both rural and urban contexts in the developing world [30], and a broad consensus has emerged which suggests that microfinance projects have helped alleviate poverty [31]. However, their usefulness in development terms, at least in some contexts, has been questioned [11,32]. The main issue behind this criticism is that given severe limitations on cash availability, relatively few people in a community can obtain credit, the amounts received by any one person are typically small and those that do obtain credit may not make the best use of it [4,16,17,29,31,32].…”
Section: Impacts Of Microfinancementioning
confidence: 99%
“…However, their usefulness in development terms, at least in some contexts, has been questioned [11,32]. The main issue behind this criticism is that given severe limitations on cash availability, relatively few people in a community can obtain credit, the amounts received by any one person are typically small and those that do obtain credit may not make the best use of it [4,16,17,29,31,32]. Hence microfinance can end up benefiting those in society who are better off as they are able to borrow relatively more and may also make better use of the credit than the poorest in society [4,16,17].…”
Section: Impacts Of Microfinancementioning
confidence: 99%
See 2 more Smart Citations